Eating Disorders and the Skin - Strumia, Renata; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
At least 40 skin signs are associated with eating disorders (EDs), and some of them are considered guiding signs because they are indicative of an otherwise hidden ED. These skin signs may arise due to starvation, self-induced vomiting, drug consumption, and concomitant psychiatric illness. The role of the dermatologist in this context is to suspect the presence of a hidden ED based on the guiding signs. With this in mind, the most important specialists in the field come together in this book to document all of the dermatological aspects of EDs. General topics such as classification of EDs, epidemiology, and medical complications are first addressed, and skin signs attributable to various causes are then discussed in a series of detailed chapters. Characteristic changes in the hair, nails, and oral cavity are also carefully documented. The closing chapters address various other related issues of interest, including pain sensitivity in patients with EDs and the effects of anorexia nervosa on skin thickness and skin collagen. Eating Disorders and the Skin will be an invaluable source of up-to-date information for both novice and experienced dermatologists, as well as other practitioners with an interest in EDs, psychiatrists, and nurses.
Classification of Eating Disorders -- Epidemiology of Eating Disorders -- Medical Complications. Treating Eating Disorders in Primary Care -- Endocrine Abnormalities in Eating Disorders -- Nutritional Status and Immunocompetence in Eating Disorders -- Skin Signs Due to Starvation -- Skin Signs Due to Self-Induced Vomiting -- Skin Signs Due to Abuse/Misuse Of Drugs -- Skin Signs Due to Psychiatric Morbidity -- Dermatologic Findings in Anorexia and Bulimia Nervosa of Childhood and Adolescence -- The Anorectic Hand(3y (B-- Hair in Eating Disorders -- Nails in Eating Disorders -- Oral Status in Eating Disorders -- Dissatisfaction With Skin Appearance Among Patients With Eating Disorders -- Aging-Related Concerns and Body Image: Possible Future Implications for Eating Disorders -- Pain Sensitivity in Anorexia Nervosa and Bulimia Nervosa -- The Effect of Anorexia Nervosa on Skin Thickness, Skin Collagen And Bone Density -- Adipose Tissue Distribution After Weight Restoration and Weight Maintenance in Women With Anorexia Nervosa -- Conclusions.s
Keywords: Medicine; Dermatology; Family medicine; Internal medicine; Psychiatry; Surgery; Medicine & Public Health; Dermatology; Oral and Maxillofacial Surgery; General Practice / Family Medicine; Internal Medicine; Psychiatry